Electrochemical device and electric device

By using lithium-rich metal oxide lithium supplement agent in the positive electrode sheet of the electrochemical device and covering the poly(3,4-ethylenedioxythiophene) layer, the problem of poor surface conductivity and structural stability after delivery of the lithium supplement agent is solved, side reactions are reduced, and the gas production and circulation performance of the battery is improved.

CN119812489AActive Publication Date: 2025-04-11ENVISION RUITAI DYNAMICS TECH (SHANGHAI) CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311310532.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

During the charging and discharging process of existing electrochemical devices, the surface conductivity and structural stability of lithium supplement material after deliquification is poor, and it is prone to side reaction with the electrolyte to produce gas, resulting in deterioration of battery performance.

Method used

The lithium-rich metal oxide is used as the lithium supplement agent in the positive electrode active material layer of the positive electrode sheet, and the poly(3,4-ethylenedioxythiophene) coating layer is coated on its surface to adapt to the volume changes of the lithium supplement agent during the high voltage deliquency process and reduce the side reaction with the electrolyte.

Benefits of technology

Through the protection of the cladding layer, the surface area exposed to the electrolyte after deliquency of the lithium supplement is reduced, side reactions are reduced, and the gas production and circulation performance of the electrochemical device is improved, making it close to the level when no lithium supplement is added.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004488243630000171
    Figure BDA0004488243630000171
  • Figure BDA0004488243630000181
    Figure BDA0004488243630000181
Patent Text Reader

Abstract

The invention provides an electrochemical device and a power utilization device, and belongs to the technical field of secondary batteries, the electrochemical device comprises a positive pole piece, the positive pole piece comprises a positive current collector and a positive active material layer arranged on the positive current collector; the positive electrode material comprises one or more of LiNi Co M < 11-a-b > O < 2 > and LiMn < 2-c > M < 2-c > O < 4 >; the positive electrode active material layer comprises a positive electrode material and a lithium supplement agent; the lithium supplement agent comprises a matrix and a coating layer, wherein the matrix comprises a lithium-rich metal oxide; the coating layer comprises poly (3, 4-ethylenedioxythiophene). According to the electrochemical device, the surface of the lithium supplement agent is coated with the PEDOT coating layer, so that side reaction gas production between residues after lithium supplement and electrolyte is reduced, and the gas production and cycle performance of the electrochemical device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to an electrochemical device and an electrical device. Background Art

[0002] During the first week of charging of electrochemical devices such as lithium-ion batteries, a solid electrolyte interface (SEI) is formed on the surface of the negative electrode, which consumes the active lithium in the positive electrode and causes irreversible capacity loss. The irreversible capacity loss of the most widely used graphite negative electrode can reach 10%, while for silicon-based and tin-based negative electrodes with high specific capacity, the irreversible capacity loss is even as high as 30% or more, which means that part of the active lithium released from the positive electrode material is irreversibly consumed. The loss of lithium will lead to reduced battery capacity, reduced coulombic efficiency, and poor cycle performance.

[0003] In the prior art, electrochemical devices usually add lithium supplements to the positive electrode active material layer of the positive electrode to compensate for the active lithium consumed by the formation of the SEI film during the first charge. However, the widely used lithium supplement materials such as Li2NiO2, Li6CoO4 and other lithium supplements are used in ternary chemical system batteries (such as lithium nickel cobalt manganese oxide LiNi x Co y Mn 1-x-y O2 batteries, etc.) will increase battery gas production, thereby deteriorating battery performance.

[0004] Therefore, it is necessary to design an electrochemical device to solve the above problems. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides an electrochemical device and an electrical device to solve the technical problem that during the charging and discharging process of the existing electrochemical device, the surface conductivity and structural stability of the lithium supplement material after delithiation are poor, and it is easy to react with the electrolyte to produce gas, which further worsens the gas production problem of the electrochemical device.

[0006] To achieve the above-mentioned object and other related objects, the present invention provides an electrochemical device, the electrochemical device comprises a positive electrode plate, the positive electrode plate comprises a positive electrode active material layer; the positive electrode active material layer comprises a positive electrode material and a lithium supplement;

[0007] The positive electrode material includes LiNi a Co b M 1 1-a-b O2 and LiMn 2-c M 2 c O4, wherein 0<a<1, 0<b<1, 0≤c<2, a+b≤1, M1 The invention comprises at least one of Mn, Al, Ti, Zr, Cu, Ca, Ta and Mg, wherein M 2 including at least one of Ni, Co, Mg, Al, Cu, Ta, Zr, Ti and Ca;

[0008] The lithium supplement comprises a matrix and a coating layer; wherein the matrix comprises a lithium-rich metal oxide; and the coating layer comprises poly(3,4-ethylenedioxythiophene).

[0009] In one example of the present invention, the lithium-rich metal oxide is Li2NiO2 or Li6CoO4.

[0010] In an example of the present invention, the coating layer has a thickness of 20 to 40 nm.

[0011] In an example of the present invention, the coating layer has a thickness of 25 to 35 nm.

[0012] In one example of the present invention, the average particle size D50 of the lithium supplement is 0.4 to 40 μm. The average particle size (D50) can be defined as the particle size corresponding to 50% of the volume accumulation in the particle size distribution curve of the particles. The average particle size (D50) can be measured by, for example, a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes ranging from the submicron range to several millimeters, thereby obtaining highly reproducible and high-resolution results.

[0013] In one example of the present invention, in the positive electrode material, the M 1 At least comprising Mn and / or Al; and / or, the M 2 At least including Ni.

[0014] In one example of the present invention, the positive electrode material includes LiNi a1 Co b1 Mn 1-a1-b1 O2、LiNi a2 Co b2 Al 1-a2-b2 O2 and LiNi c1 Mn 2-c1 One or more of O4, wherein 0<a1, a2<1, 0<b1, b2<1, 0<c1<2, a1+b1<1, a2+b2<1.

[0015] In an example of the present invention, the lithium supplement agent accounts for 0.1-10 wt % of the positive electrode active material layer.

[0016] In an example of the present invention, the lithium supplement accounts for 2-7 wt % of the positive electrode active material layer.

[0017] The present invention also provides an electrical device, which includes the electrochemical device described in any of the above examples.

[0018] The present invention provides an electrochemical device, wherein a lithium-rich metal oxide lithium supplement is used in a positive electrode active material layer of a positive electrode plate in combination with a layered structure or a spinel structure positive electrode material, and a coating layer containing poly(3,4-ethylenedioxythiophene) is coated on the surface of the lithium supplement, so that the coating layer having both conductivity and elasticity is used to adapt to the volume change caused by the shrinkage and rupture of the lithium supplement during the high-voltage delithiation process, so as to form a continuous and good protection effect on the surface of the lithium supplement, thereby reducing the surface area of ​​the lithium supplement exposed to the electrolyte after the lithium supplement is delithiated, thereby ensuring smooth electron transmission at the interface of the lithium supplement and reducing the side reaction at the interface of the lithium supplement / electrolyte, so as to improve the gas generation and cycle performance of the electrochemical device. DETAILED DESCRIPTION

[0019] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0020] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0021] Typically, electrochemical devices (such as secondary batteries) usually include positive electrode materials, negative electrode materials, electrolytes, diaphragms, and corresponding connecting accessories and circuits. During the battery charging and discharging process, active ions (lithium ions) are embedded and removed back and forth between the positive electrode and the negative electrode. The diaphragm is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing lithium ions to pass through. The electrolyte between the positive electrode and the negative electrode mainly plays the role of conducting active ions.

[0022] During the first charge of the battery, lithium ions are released from the positive electrode active material, conducted through the electrolyte, and embedded in the negative electrode active material. During this process, some lithium ions participate in the reaction of forming a solid electrolyte interface (SEI) film on the surface of the negative electrode active material, resulting in loss of active lithium. In addition, during the subsequent cycle charge and discharge process and storage of the battery, the repair and growth of the SEI film, as well as the side reactions of the electrolyte on the surface of the lithium-embedded negative electrode may occur, which will irreversibly consume lithium ions.

[0023] To this end, additional active lithium can be provided through a pre-lithium replenishment scheme, thereby compensating for the loss of active lithium. In the existing positive electrode lithium replenishment scheme, a lithium replenisher that is compatible with the battery chemical system is usually added to the positive electrode plate, such as a lithium-rich metal oxide with a surface-coated oxide layer. Lithium-rich metal oxides such as Li2NiO2 and Li6CoO4 are adapted to the battery's charge and discharge voltage range, and release lithium ions when the battery is charged, which can compensate for the irreversible loss of active lithium during the formation of the SEI film during the first charge of the battery and the subsequent cycle process and storage process. The metal oxide layer can improve the interface stability of the lithium replenisher to reduce the interface side reactions between the lithium replenisher and the electrolyte, thereby reducing the negative impact on the battery's performance.

[0024] Lithium replenishers can replenish lithium ions lost in the battery due to the formation of SEI film and other reasons, thereby ensuring the energy of the battery. However, in actual applications, the addition of lithium replenishers will have additional negative effects on the performance of secondary batteries. For example, for the positive electrode lithium replenishment scheme of batteries with ternary layered structure or spinel structure positive electrode material system, the lithium replenishers currently used will greatly increase the gas production of the battery, thereby affecting the battery cycle performance and safety performance. The above-mentioned effects are more serious under high temperature conditions (for example, above 45°C, such as 45°C to 80°C or 45°C to 60°C, etc.).

[0025] The inventors found that the lithium supplement agent has difficulty adapting to the higher voltage of the battery due to its own characteristics during the lithium desorption process in the high voltage range, and after desorption, it reacts with the electrolyte to produce additional gas. For secondary batteries with layered structure materials or spinel structure materials as the main positive electrode materials, they have higher charge and discharge voltages than batteries with lithium iron phosphate as the positive electrode material. For example, the full charge voltage of ternary materials is 4.2V~4.4V, and the full charge voltage of nickel manganese spinel materials is 4.7V~5.0V. The lithium supplement will be over-delithiated under such high voltage, and the surface of the lithium supplement will collapse significantly and form deep cracks. Conventional coating layers such as metal oxides are difficult to adapt to such a large volume change and are easily torn during the lithium insertion and extraction process, thereby exposing the surface cracks of the lithium-rich metal oxide to the electrolyte. After excessive lithium removal, the lithium-rich metal oxide is likely to leave residual compounds such as metal oxides or Li-MO (lithium-containing metal oxides) on the surface. These residual substances have extremely strong reactivity with the electrolyte. When the residual substances are directly exposed to the electrolyte, they will react with the electrolyte to cause gas production, thereby worsening the gas production problem of the secondary battery. Therefore, for the pre-lithium replenishment scheme of secondary batteries with layered structure materials or spinel structure materials as the main positive electrode materials, how to suppress the storage gas generation of the battery while maintaining the high energy density of the battery by adding lithium replenishers is an urgent problem to be solved.

[0026] In order to solve the above problems, the present invention provides an electrochemical device, in which a lithium-rich metal oxide coated with poly(3,4-ethylenedioxythiophene) is used as a lithium supplement in the positive electrode plate of the electrochemical device. The coating layer on the surface of the lithium supplement that has both conductivity and elasticity can adapt to the volume change caused by the shrinkage and rupture of the lithium supplement during the high-voltage lithium insertion and extraction process, and form a continuous and good protection effect on the surface of the lithium supplement, thereby ensuring smooth electron transmission at the interface of the lithium supplement and reducing the side reaction at the interface of the lithium supplement / electrolyte, greatly improving the gas production and cycle performance of the electrochemical device, so that the gas production and cycle performance of the electrochemical device with the lithium supplement added reaches the level when the lithium supplement is not added.

[0027] The present invention provides an electrochemical device, a specific embodiment of which is a battery including one or more "battery cells". The "battery cell" refers to a battery cell that can be charged and discharged independently. The "battery cell" includes a positive electrode plate, a negative electrode plate, an electrolyte, a diaphragm, and corresponding connecting accessories and circuits. The positive electrode plate includes a positive electrode collector and a positive electrode active material layer disposed on the positive electrode collector, and the positive electrode active material layer includes a positive electrode material, a lithium supplement, a conductive agent, and a binder; the negative electrode plate includes a negative electrode collector and a negative electrode active material layer disposed on the negative electrode collector, and the negative electrode active material layer includes a negative electrode material, a conductive agent, a thickener, and a binder. In the electrochemical device, the positive and negative electrode materials can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for lithium ions to be transmitted between the positive electrode plate and the negative electrode plate, and the diaphragm can pass lithium ions but is not conductive, thereby separating the positive electrode plate and the negative electrode plate to prevent short circuit. It should be noted that the type of negative electrode material used in the negative electrode plate can be any negative electrode active material known in the art. For example, the negative electrode material can be a carbon-based material (such as graphite, hard carbon or soft carbon), a silicon-based material (such as silicon oxide) or a carbon-silicon composite material.

[0028] The above-mentioned positive electrode materials include layered structure materials, such as LiNi a Co b M 1 1-a-b O2, and spinel structure materials such as LiMn 2-c M 2 c O4, one or more of which, 0<a<1, 0<b<1, 0≤c<2, a+b≤1, M 1 The invention comprises at least one of Mn, Al, Ti, Zr, Cu, Ca, Ta and Mg, wherein M 2 Includes at least one of Ni, Co, Mg, Al, Cu, Ta, Zr and Ca.

[0029] Among them, the electrochemical device has a higher energy density and full charge voltage under the above-mentioned positive electrode material system. For example, when the positive electrode material is a layered structure material (such as a ternary material), the full charge voltage of the electrochemical device can reach 4.2V to 4.4V; when the positive electrode material is a spinel structure material (such as a nickel-manganese spinel material), the full charge voltage of the electrochemical device can reach 4.7V to 5.0V.

[0030] Layered structure material LiNi a Co b M 1 1-a-b O2, M 1 The element is selected from at least one of Mn, Al, Ti, Zr, Cu, Ca, Ta and Mg. 1The element may be any one of the above-listed element types, such as Mn, Al, Ti, Zr, Cu, Ca, Ta or Mg, etc.; M 1 The element may also be any combination of two or more of the above-listed element types, for example, M 1 The element may be a combination of Mn and Al, or a combination of Mn and Zr, or a combination of Mn and Mg, or a combination of Al and Ti, or a combination of Al and Zn, or a combination of Mn, Al and Ga, or a combination of Mn, Al, Cu and Mg, etc., which are not listed here one by one.

[0031] Spinel structure material LiMn 2-c M 2 c O4, M 2 The element is selected from at least one of Ni, Co, Mg, Al, Cu, Ta, Zr, Ti and Ca. 2 The element may be any one of the above-listed element types, such as Ni, Co, Mg, Al, Cu, Ta, Zr, Ti or Ca, etc.; M 2 The element may also be any combination of two or more of the above-listed element types, for example, M 2 The element can be a combination of Ni and Al, or a combination of Ni and Co, or a combination of Ni and Mg, or a combination of Ni and Cu, or a combination of Al and Ta, or a combination of Ti and Cu, or a combination of Ti, Ta and Zr, or a combination of Ni, Co and Al, or a combination of Ni, Co and Zr, or a combination of Ni, Co, Cu and Mg, and so on, which are not listed here one by one.

[0032] In addition, when M 1 Elements and M 2 When the elements are two or more combinations, there is no restriction on the ratio of each element in the combination. 1 Elements and M 2 The element may be a type of element not listed above.

[0033] The above-mentioned lithium supplement includes a matrix and a coating layer, the coating layer covers at least part of the matrix surface, for example, the coating layer covers the entire surface of the matrix particles, or the coating layer covers part of the surface of the matrix particles; the matrix includes a lithium-rich metal oxide, and the coating layer includes poly (3,4-ethylenedioxythiophene), that is, Poly (3,4-ethylenedioxythiophene), referred to as PEDOT.

[0034] Among them, the lithium-rich metal oxide has a higher lithium deintercalation capacity and can release more active lithium during the battery charging process, thereby more effectively compensating for the irreversible loss of active lithium in the battery, so that the battery can have a higher cycle life or storage life under high temperature conditions. It should be noted that the lithium-rich metal oxide can be selected from any corresponding lithium metal oxide material known in the art according to the type of positive electrode material used. For example, in a specific embodiment of the present invention, in order to cooperate with the positive electrode material mainly composed of layered structure materials and / or spinel structure materials in the electrochemical device, the lithium-rich metal oxide uses Li2NiO2 or Li6CoO4.

[0035] PEDOT has a good elastic modulus, and the coating formed by PEDOT accumulation can adapt to the volume change caused by the shrinkage and rupture of the particles of the lithium-rich metal oxide matrix during the process of lithium insertion and extraction, so that it can continue to adhere to the surface of the lithium-rich metal oxide to form a lasting protective effect on the interface of the lithium supplement. PEDOT attached to the surface of the substrate has good compatibility with the electrolyte. It can isolate the substrate from direct contact with the electrolyte while ensuring that it will not react with the electrolyte during the electron transmission process, thereby effectively reducing the side reactions at the lithium supplement / electrolyte interface and greatly improving the high-temperature gas production and cycle performance of the battery. In addition, since the lithium-rich metal oxide itself has poor electronic conductivity, the existing metal oxide coating may deteriorate the DC internal resistance of the battery and affect the battery's rate performance. As a high-quality conductive polyelectrolyte complex, PEDOT has excellent conductivity and will not increase the internal resistance of the battery too much.

[0036] In some embodiments, the coating layer has a thickness of 20 to 40 nm, for example, the coating layer may be 20 nm, 25 nm, 30 nm, 35 nm or 40 nm. The coating layer has good conductivity and elastic modulus within the above thickness range. If the coating layer is thin, the elastic modulus of the coating layer may not be sufficient to adapt to the volume change caused by the shrinkage and rupture of the particles in the matrix during the first lithium insertion and extraction process. It is difficult to completely cover the surface of the coated matrix after the lithium supplement is removed, so that part of the surface of the matrix is ​​exposed to the electrolyte, and the improvement effect on the side reaction of the lithium supplement / electrolyte interface is poor. If the coating layer is thick, the PEDOT coating layer will affect the release of lithium ions from the lithium supplement, hinder ion transmission, and increase the internal resistance of the electrochemical device.

[0037] In some embodiments, the thickness of the coating layer may be 25 to 35 nm, for example, the thickness of the coating layer may be 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm or 35 nm. Further, the thickness of the coating layer may be 30 nm. When the thickness of the coating layer is within the above range, the elastic modulus and conductivity of the coating layer on the surface of the lithium supplementing agent are optimally balanced.

[0038] In some embodiments, the elastic modulus of the coating layer is 2 to 4 GPa, for example, the elastic modulus of the coating layer may be 2 GPa, 2.5 GPa, 3 GPa, 3.5 GPa or 4 GPa. Since the coating layer has the elastic modulus in the above range, it can adapt to the volume change of the lithium supplement agent under high voltage, so that the coating layer can maintain a large area of ​​coating on the surface of the substrate after the lithium supplement agent is de-lithiated.

[0039] In some embodiments, the layered structure material LiNi a Co b M 1 1-a-b O2, M 1 The elements at least include Mn and / or Al. Optionally, the layered structure material uses a ternary material, for example, LiNi a1 Co b1 Mn 1-a1-b1 O2、LiNi a2 Co b2 Al 1-a2-b2 O2, wherein 0<a1, a2<1, 0<b1, b2<1, a1+b1<1, a2+b2<1; further, the ternary material may be LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Mn 0.05 O2、LiNi 0.8 Co 0.1 Al 0.1 O2 and LiNi 0.8 Co 0.15 Al 0.05 At least one of O2.

[0040] In some embodiments, the spinel structure material LiMn 2-c M 2 c O4, M 2 The element at least includes Ni. Optionally, the spinel structure material adopts nickel-manganese spinel material, that is, LiNi c1 Mn 2-c1 O4, wherein 0<c1<2; further, the nickel manganese spinel material may be LiNi 0.5±0.2 Mn 1.5±0.2 O4.

[0041] In the above embodiment, the positive electrode material includes LiNi a1 Co b1 Mn 1-a1-b1 O2、LiNi a2 Co b2 Al1-a2-b2 O2 and LiNi c1 Mn 2-c1 One or more of O4, wherein 0<a1, a2<1, 0<b1, b2<1, 0<c1<2, a1+b1<1, a2+b2<1.

[0042] In some embodiments, the mass content of the lithium supplement agent in the positive electrode active material layer is 0.1-10wt%, for example, it can be 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%; optionally, the mass content of the lithium supplement agent in the positive electrode active material layer is 2-7wt%, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt% or 7wt%. When the mass content of the lithium supplement agent in the positive electrode active material layer is within the above range, the loss of active lithium in the positive electrode active material layer can be compensated as much as possible without excessively affecting the energy density of the battery. Among them, when the mass content of the lithium supplement agent is lower than the above range, it may not be able to make up for the loss of active lithium in the positive electrode active material layer; when the mass content of the lithium supplement agent is higher than the above range, it may cause insufficient reversible lithium insertion vacancies in the positive electrode active material layer, affecting the energy density of the battery.

[0043] In addition, the present invention further provides an electric device, the electric device includes the electrochemical device described in any of the above embodiments, the electrochemical device can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0044] The composition and preparation method of the electrochemical device provided by the present invention are described in detail below:

[0045] Preparation of positive electrode sheet: positive electrode material, lithium supplement, conductive agent and binder are mixed in a mass ratio of (87 to 97): (0.1 to 10): 1.5: 1.5, and the mass ratio can be 94: 3: 1.5: 1.5, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the conductive agent can be selected from at least one of carbon black (Super P), acetylene black, carbon nanotubes (CNT), graphene, nano carbon fiber (VGCF) and other conductive materials, for example, the conductive agent is SP and CNT, and the mass ratio of SP and CNT is 1: 0.5; the binder can be selected from at least one of PVDF, PTFE and the like.

[0046] The preparation method of the lithium supplement comprises the following steps:

[0047] S1, mixing and sintering a metal precursor and a lithium source to obtain a lithium-rich metal oxide matrix;

[0048] S2. 3,4-ethylenedioxythiophene monomer (EDOT) and an initiator are blown through a substrate, and a poly(3,4-ethylenedioxythiophene) coating layer, namely PEDOT, is deposited on the surface of the substrate by oxidative chemical vapor deposition (CVD) to obtain a lithium supplement.

[0049] In step S1, the lithium source is at least one of Li2O, LiOH, Li2CO3, LiNO3, Li2C2O4, and CH3COOLi. Optionally, the lithium source uses LiOH; the metal element of the metal precursor is Ni or Co, and the precursor of the Ni element can be Ni oxide, hydroxide, organic salt or inorganic salt, for example, it can be at least one of NiO, Ni(OH)2, NiSO4, Ni(NO3)2, and Ni(CH3COO)2; the precursor of the Co element can be Co oxide, hydroxide, organic salt or inorganic salt, for example, it can be at least one of Co3O4, Co(OH)2, CoCO3, CoOOH, and Co3(PO4)2.

[0050] In step S2, the thickness of the coating layer deposited on the surface of the substrate is controlled by adjusting the flow rate of EDOT and initiator blowing the substrate or the deposition reaction time.

[0051] Preparation of negative electrode sheet: negative electrode materials such as graphite, conductive agent acetylene black, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water is added, and the mixture is stirred and mixed to obtain negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes;

[0052] Preparation of diaphragm: The diaphragm is made of PE or PP porous membrane, and PP / PE / PP porous membrane can be selected, with a thickness of 9μm to 18μm, such as 9μm, 12μm, 16μm or 18μm; the air permeability is 180s / 100mL to 380s / 100mL, such as 180s / 100mL, 280s / 100mL or 380s / 100mL; the porosity is 30% to 50%, such as 30%, 40% or 50%.

[0053] Preparation of electrolyte: Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0054] Assembling electrochemical devices (secondary batteries): stacking the prepared positive electrode sheets, separators, and negative electrode sheets in sequence, with the separator placed between the positive and negative electrode sheets to play a role of isolation. Then wrapping with aluminum plastic film, injecting the above-prepared electrolyte after drying, and finally preparing a soft-pack battery (i.e., lithium-ion secondary battery) with a capacity of 1Ah after packaging, standing, and formation.

[0055] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.

[0056] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.

[0057] Example 1

[0058] This embodiment provides a secondary battery, wherein the positive electrode plate of the secondary battery includes a positive electrode material and a lithium supplement. The positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1O2, the lithium supplement agent is based on Li2NiO2, and a PEDOT coating layer with a thickness of 15nm is deposited on the surface of the substrate.

[0059] The preparation process of the lithium supplement is as follows:

[0060] S1. Mix the dehydrated Ni(OH)2 precursor and LiOH, add Al2O3 accounting for 0.2wt% of the mass fraction of the prepared matrix, and sinter the mixture at 800°C in a nitrogen atmosphere for 20h to obtain a sintered material; then crush the sintered material and continue to sinter it at 800°C in a nitrogen atmosphere for 10h to obtain a Li2NiO2 matrix;

[0061] S2. Blow 3,4-ethylenedioxythiophene monomer (EDOT) and an initiator through the substrate, and deposit a PEDOT coating layer with a thickness of 15 nm on the surface of the substrate by a CVD method to obtain a lithium supplement.

[0062] The preparation process of the secondary battery is as follows:

[0063] (1) Preparation of positive electrode sheet: The positive electrode material is mixed with the lithium supplement agent, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) prepared above in a weight ratio of 94:3:1.5:1.5, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred thoroughly to obtain a positive electrode slurry; the mixture is stirred under the action of a vacuum mixer until the system is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 16μm aluminum foil current collector, and the aluminum foil current collector is then dried at room temperature and transferred to an oven to dry at 80℃ to 120℃ for 6h, and then cold pressed and cut to obtain a positive electrode sheet, wherein the thickness of the positive electrode active material layer is about 50μm.

[0064] (2) Preparation of negative electrode sheets: negative electrode material graphite, conductive agent acetylene black, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water was added, and the solid content of the slurry was adjusted to 55%, and then the mixture was fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on both sides of an 8 μm negative electrode current collector copper foil; after drying at room temperature, the mixture was transferred to an oven for drying, and then cold pressed, cut and other processes were performed to obtain a negative electrode sheet, wherein the thickness of the negative electrode active material layer was about 50 μm.

[0065] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 was dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0066] (4) Diaphragm preparation: The diaphragm is a 9 μm polyethylene diaphragm coated on both sides with a ceramic coating with a thickness of 2 μm.

[0067] (5) Assembling the battery: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, with the separator placed between the positive and negative electrode sheets to play a role of isolation. Then, the sheet is wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and sealed after injecting 3.0g / Ah of electrolyte. After standing, hot and cold pressing, formation, clamping, and capacity division, a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is finally prepared.

[0068] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.

[0069] Example 2

[0070] This embodiment provides a secondary battery of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the lithium supplementing agent substrate is 20 nm by controlling the deposition time.

[0071] Example 3

[0072] This embodiment provides a secondary battery of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 27 nm by controlling the deposition time.

[0073] Example 4

[0074] This embodiment provides a secondary battery of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 30 nm by controlling the deposition time.

[0075] Example 5

[0076] This embodiment provides a secondary battery of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 40 nm by controlling the deposition time.

[0077] Example 6

[0078] This embodiment provides a secondary battery of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 50 nm by controlling the deposition time.

[0079] Example 7

[0080] This embodiment provides a secondary battery similar to that of embodiment 4. The difference between this embodiment and embodiment 4 is that the positive electrode material used in the secondary battery of embodiment 7 is LiNi 0.8 Co 0.15 Al 0.05 O2 material.

[0081] Example 8

[0082] This embodiment provides a secondary battery similar to that of embodiment 4. The difference between this embodiment and embodiment 4 is that the positive electrode material used in the secondary battery of embodiment 8 is LiNi 0.5 Mn 1.5 O4 material.

[0083] Example 9

[0084] This embodiment provides a secondary battery of the same system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that the lithium supplement in the secondary battery is based on Li6CoO4, and a PEDOT coating layer with a thickness of 15 nm is deposited on the surface of the substrate. The preparation process of the lithium supplement is as follows:

[0085] S1. Mix the dehydrated Co(OH)2 precursor and LiOH, add Al2O3 accounting for 0.2wt% of the mass fraction of the prepared matrix, and sinter the mixture at 800°C in a nitrogen atmosphere for 20h to obtain a sintered material; then crush the sintered material and continue to sinter it at 800°C in a nitrogen atmosphere for 10h to obtain a Li6CoO4 matrix;

[0086] S2. Blow 3,4-ethylenedioxythiophene monomer (EDOT) and an initiator through the substrate, and deposit a PEDOT coating layer with a thickness of 15 nm on the surface of the substrate by a CVD method to obtain a lithium supplement.

[0087] Example 10

[0088] This embodiment provides a secondary battery of the same system as that of Embodiment 9. The difference between this embodiment and Embodiment 9 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 20 nm by controlling the deposition time and other methods.

[0089] Embodiment 11

[0090] This embodiment provides a secondary battery of the same system as that of Embodiment 9. The difference between this embodiment and Embodiment 9 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 30 nm by controlling the deposition time and other methods.

[0091] Example 12

[0092] This embodiment provides a secondary battery of the same system as that of Embodiment 9. The difference between this embodiment and Embodiment 9 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 40 nm by controlling the deposition time and other methods.

[0093] Embodiment 13

[0094] This embodiment provides a secondary battery of the same system as that of Embodiment 9. The difference between this embodiment and Embodiment 9 is that in step S2, the thickness of the PEDOT coating layer deposited on the surface of the substrate is 50 nm by controlling the deposition time and other methods.

[0095] Embodiment 14

[0096] This embodiment provides a secondary battery similar to that of embodiment 11. The difference between this embodiment and embodiment 11 is that the positive electrode material used in the secondary battery of embodiment 14 is LiNi 0.8 Co 0.15 Al 0.05 O2 material.

[0097] Embodiment 15

[0098] This embodiment provides a secondary battery similar to that of embodiment 11. The difference between this embodiment and embodiment 11 is that the positive electrode material used in the secondary battery of embodiment 15 is LiNi 0.5 Mn 1.5 O4 material.

[0099] Comparative Example 1

[0100] Comparative Example 1 provides a secondary battery of the same system as Example 1, wherein the lithium supplement agent assembled in the secondary battery uses Li2NiO2 as a matrix, and the PEDOT coating layer is not coated on the surface of the matrix, but an Al2O3 coating layer is coated on the surface of the matrix. The preparation process of the lithium supplement agent is as follows:

[0101] S1. Mix the dehydrated Ni(OH)2 precursor and LiOH, add Al2O3 accounting for 0.2wt% of the mass fraction of the prepared matrix, and sinter the mixture at 800°C in a nitrogen atmosphere for 20h to obtain a sintered material; then crush the sintered material and continue to sinter it at 800°C in a nitrogen atmosphere for 10h to obtain a Li2NiO2 matrix;

[0102] S2. The matrix is ​​uniformly mixed with 0.2 wt% Al2O3, and after mixing, the mixture is sintered at 400°C in a nitrogen atmosphere for 8 hours to obtain a lithium supplement.

[0103] Comparative Example 2

[0104] Comparative Example 2 provides a secondary battery similar to Comparative Example 1. The difference between Comparative Example 2 and Comparative Example 1 is that the positive electrode material used in the secondary battery in Comparative Example 2 is LiNi 0.8 Co 0.15 Al 0.05 O2 material.

[0105] Comparative Example 3

[0106] Comparative Example 3 provides a secondary battery similar to Comparative Example 1. The difference between Comparative Example 3 and Comparative Example 1 is that the positive electrode material used in the secondary battery in Comparative Example 3 is LiNi 0.5 Mn 1.5 O4 material.

[0107] Comparative Example 4

[0108] Comparative Example 4 provides a secondary battery of the same system as Example 9, wherein the lithium supplement agent assembled in the secondary battery uses Li6CoO4 as a matrix, and the PEDOT coating layer is not coated on the surface of the matrix, but an Al2O3 coating layer is coated on the surface of the matrix. The preparation process of the lithium supplement agent is as follows:

[0109] S1. Mix the dehydrated Co(OH)2 precursor and LiOH, add Al2O3 accounting for 0.2wt% of the matrix mass fraction, and sinter for 20h at 800℃ in a nitrogen atmosphere to obtain a sintered material; then crush the sintered material and continue to sinter for 10h at 800℃ in a nitrogen atmosphere to obtain a Li2NiO2 matrix;

[0110] S2. The matrix is ​​uniformly mixed with 0.2 wt% Al2O3, and after mixing, the mixture is sintered at 400°C in a nitrogen atmosphere for 8 hours to obtain a lithium supplement.

[0111] Comparative Example 5

[0112] Comparative Example 5 provides a secondary battery similar to Comparative Example 4. The difference between Comparative Example 5 and Comparative Example 4 is that the positive electrode material used in the secondary battery in Comparative Example 5 is LiNi 0.8 Co 0.15 Al 0.05 O2 material.

[0113] Comparative Example 6

[0114] Comparative Example 6 provides a secondary battery similar to Comparative Example 4. The difference between Comparative Example 6 and Comparative Example 4 is that the positive electrode material used in the secondary battery in Comparative Example 6 is LiNi 0.5 Mn 1.5 O4 material.

[0115] The lithium supplements prepared in Examples 1 to 15 and Comparative Examples 1 to 6 were tested for gram capacity, and the lithium ion secondary batteries equipped with the lithium ion supplements prepared in Examples 1 to 15 and Comparative Examples 1 to 6 were tested for gas production performance and DCR (Direct Current Resistance) to verify the excellent gas production performance and cycle performance of the electrochemical devices corresponding to the different Examples and Comparative Examples. The test results are shown in Table 1, and the test methods are as follows:

[0116] (1) Lithium supplement capacity test:

[0117] The lithium supplement material prepared in the above embodiments and comparative examples, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 85:10:5, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a positive electrode collector aluminum foil, and a positive electrode plate is prepared through drying, cold pressing, slitting and other processes, and a 2032 button half-cell is assembled with lithium metal as a negative electrode plate;

[0118] At 25°C, at a current density of 0.02A / g, in the test voltage range of 3V (discharge cut-off voltage) to 4.3V (charge cut-off voltage) (when the lithium supplement is in layered ternary materials such as LiNi 0.8 Co 0.1 Mn 0.1 O2, when used in the system), or at 3V (discharge cut-off voltage) to 4.95V (charge cut-off voltage) (when the lithium supplement is in LiNi 0.5 Mn 1.5 O4 system), the button half-cell is subjected to the first charge and discharge test, the charge / discharge capacity of the button half-cell is measured and then divided by the mass of the lithium supplement to obtain the gram capacity of the lithium supplement.

[0119] (2) Gas production performance test of soft pack battery:

[0120] The initial volume V1 of the secondary battery prepared above was tested after full charging, and then the secondary battery was stored in a high temperature cabinet at 60°C. The secondary battery was recharged and the volume was tested every 7 days. After 56 days, the volume of the secondary battery tested was V2, and (V2-V1) / V1 was the gas production growth.

[0121] (3) Soft pack battery DCR test method:

[0122] The capacity of the secondary battery prepared above was adjusted to 50% SOC (State Of Charge), and then the DCR of the secondary battery was tested by discharging at a constant current rate of 4C for 30s.

[0123] Table 1: Gram capacity test results of lithium supplements prepared in Examples 1 to 15 and Comparative Examples 1 to 6, and gas generation test and DCR test results of corresponding secondary batteries

[0124]

[0125]

[0126] By comparing the test results of Examples 1 to 8 and Comparative Examples 1 to 3, and Examples 9 to 15 and Comparative Examples 4 to 6, it can be seen that the use of lithium-rich metal oxides coated with PEDOT as lithium supplements in secondary batteries can effectively improve the gas production performance of secondary batteries with ternary positive electrode systems and spinel positive electrode systems. Since the PEDOT coating layer has a good elastic modulus, it can adapt to the shrinkage and rupture of particles of the lithium supplement during the first lithium insertion and extraction process of the lithium supplement at high voltage, forming a continuous and good protection effect on the surface of the lithium supplement, reducing the side reactions at the lithium supplement / electrolyte interface, and effectively improving the storage gas production problem of high energy density secondary batteries.

[0127] The test results show that compared with the high gas production growth rate of more than 30% after 56 days of storage when the secondary battery is coated with Al2O3, the gas production growth rate of the corresponding secondary battery after 56 days of storage can be reduced by at least 10% when the lithium supplement agent is coated with PEDOT. For example, after PEDOT coating, the gas production growth rate of the NCM ternary system secondary battery with Li2NiO2 as the lithium supplement agent matrix after 56 days of storage is reduced from 34.7% to below 23.9%. The gas production growth rate of the nickel-manganese spinel system secondary battery with O2 as the lithium supplement matrix decreased from 42.9% to 23.1% after 56 days of storage; while the gas production growth rate of the NCM ternary system secondary battery with Li6CoO4 as the lithium supplement matrix decreased from 34.7% to below 23.9% after 56 days of storage; the gas production growth rate of the nickel-manganese spinel system secondary battery with Li6CoO4 as the lithium supplement matrix decreased from 44.6% to below 21.5% after 56 days of storage.

[0128] By comparing the test results of Examples 1 to 6 and Examples 9 to 13, it can be seen that as the thickness of the PEDOT coating layer on the surface of the lithium supplement agent increases, the protective effect of the coating layer on the substrate is further improved, and the corresponding secondary battery storage gas generation is also reduced, and the gas generation problem of the secondary battery is further improved. For example, for the NCM ternary system secondary battery with Li2NiO2 as the lithium supplement agent matrix, the gas generation growth rate after the secondary battery is stored for 56 days is gradually reduced from 23.9% when the thickness of the lithium supplement agent coating layer is 15nm to 12.6% when the thickness of the lithium supplement agent coating layer is 50nm; for the NCM ternary system secondary battery with Li6CoO4 as the lithium supplement agent matrix, the gas generation growth rate after the secondary battery is stored for 56 days is gradually reduced from 29.3% when the thickness of the lithium supplement agent coating layer is 15nm to 13.2% when the thickness of the lithium supplement agent coating layer is 50nm.

[0129] In addition, due to the good electronic conductivity of the PEDOT material itself, the reaction kinetics of the positive electrode sheet was improved by using the PEDOT-coated lithium supplement. After using the PEDOT-coated lithium supplement, the DCR of the secondary battery was reduced by 3.9%.

[0130] Comparing the test results of Examples 1 to 6 and Examples 9 to 13, it can be seen that when the coating thickness on the surface of the lithium supplement agent is in an appropriate range, that is, when the coating thickness is 15 to 30 nm, the storage gas production and DCR of the secondary battery decrease with the increase of the coating thickness of the lithium supplement agent. However, since PEDOT is not a good lithium ion conductor, when the coating thickness on the surface of the lithium supplement agent is above 30 nm, the excessively thick PEDOT coating will affect the release of lithium ions from the lithium supplement agent, reduce the charge and discharge capacity of the lithium supplement agent, and deteriorate the conductivity of the positive electrode sheet, resulting in an increase in the internal resistance of the electrochemical device, affecting the cycle performance of the electrochemical device. It can be seen that when the coating thickness of the lithium supplement agent is 25 nm to 35 nm, especially 30 nm, the lithium supplement agent has the best effect on improving the gas production and DCR of high-capacity secondary batteries.

[0131] By comparing Example 7 with Comparative Example 2, Comparative Example 8 with Comparative Example 3, Comparative Example 14 with Comparative Example 5, and Comparative Example 15 with Comparative Example 6, it can be found that the improvement effect of the above-mentioned lithium supplement coating layer on gas production is still significant in the secondary batteries of the NCA ternary positive electrode system and the spinel positive electrode system.

[0132] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, and the positive electrode sheet comprises a positive electrode active material layer; The positive electrode active material layer includes a positive electrode material and a lithium supplement; The positive electrode material includes LiNi a Co b M 1 1-a-b O2 and LiMn 2-c M 2 c O4, wherein 0<a<1, 0<b<1, 0≤c<2, a+b≤1, M 1 The invention comprises at least one of Mn, Al, Ti, Zr, Cu, Ca, Ta and Mg, wherein M 2 including at least one of Ni, Co, Mg, Al, Cu, Ta, Zr, Ti and Ca; The lithium supplement comprises: a substrate, the substrate comprising a lithium-rich metal oxide; The coating layer comprises poly (3,4-ethylenedioxythiophene).

2. The electrochemical device according to claim 1, characterized in that: The lithium-rich metal oxide is Li2NiO2 or Li6CoO4.

3. The electrochemical device according to claim 1, characterized in that: The coating layer has a thickness of 20 to 40 nm.

4. The electrochemical device according to claim 3, characterized in that: The coating layer has a thickness of 25 to 35 nm.

5. The electrochemical device according to claim 1, characterized in that: The average particle size D50 of the lithium supplement agent is 0.4-40 μm.

6. The electrochemical device according to claim 1, characterized in that: In the positive electrode material, the M 1 At least Mn and / or Al; and / or, the M 2 At least including Ni.

7. The electrochemical device according to claim 6, characterized in that: The positive electrode material includes LiNi a1 Co b1 Mn 1-a1- b1 O2、LiNi a2 Co b2 Al 1-a2-b2 O2 and LiNi c1 Mn 2-c1 One or more of O4, wherein 0<a1, a2<1, 0<b1, b2<1, 0<c1<2, a1+b1<1, a2+b2<1.

8. The electrochemical device according to claim 1, characterized in that: The mass content of the lithium supplement agent in the positive electrode active material layer is 0.1 to 10 wt %.

9. The electrochemical device according to claim 8, characterized in that: The mass content of the lithium supplement agent in the positive electrode active material layer is 2-7 wt %.

10. An electrical device, characterized in that: The electrical device comprises the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for coating spinel lithium manganate positive electrode material through liquid-phase in-situ polymerization

    CN107611358A

  • Positive electrode, electrochemical device, and electronic device

    CN112582579A

  • Composite lithium supplement additive and preparation method and application thereof

    CN113036106A

  • Lithium ion secondary battery, preparation method thereof, battery module, battery pack and device

    CN115803932A

  • Lithium supplement agent, preparation method thereof and positive electrode material of lithium ion battery

    CN115939349A